Methods of Measuring the Efficiency of Commercial Banks: an Example of Polish Banks - Wozniewska, Grazyna (Ekonomika, 2008)
Efficiency analysis is essential for the evaluation of banks’ performance. To estimate banks’ efficiency, we can apply different methods. Analysis of financial indicators is the most popular efficiency analysis method in banks, but the number of financial indicators can be really big and make the interpretation of the results more difficult. Another way to estimate efficiency measures is the nonparametric frontier method - Data Envelopment Analysis (DEA). This method has become increasingly popular in measuring bank efficiency in the countries with developed banking systems. The main aim of this article is to present the results of efficiency analysis, computed by means of both methods, i. e. the classical index of balance sheet characteristics and the non-parametric DEA method. The analysis was carried out in the biggest banks operating in Poland in 2000-2007. The empirical results show that the efficiency measures give a similar although not identical picture of Polish commercial banks’ performance. These results (yielded by both methods) are complementary to each other and suggest that the non-parametric DEA method is really valuable and worth applying in bank practice. The work presents also the reasons that would explain the achieved results. It also compares both methods, their potentials and limitations in applying them to banking.